Building Better Dictation Skills - Buonviri, Nathan O. (Rowman & Littlefield Publishers, 2015)
Melodic dictation plays an important role in music theory classes, but instruction is often based on tradition rather than research. Dictation teachers and students do not just need more exercises and drills; they need to see deeper into the materials, consider how we connect to them, and practice wisely. Building Better Dictation Skills offers teachers and students the “why” and “how” of melodic dictation, through research-based exercises aimed at developing proactive musical listening. During dictation, students must actively involve themselves in the unfolding of an unfamiliar melody—using all of their musical skills in a concerted effort—to get into the composer’s mind and understand what is played. The author’s published research, on which this book is based, provides a level of insight unlikely to be discovered simply through drilling more melodies. Building Better Dictation Skills provides music educators and students with a concise, specific, and affordable resource that focuses on what they really need: dictation strategies aimed at learning beyond the “right answer.”